Urinary incontinence in patients of Duchenne syndrome - Alves , Ricardo Antônio Pinho; Rodrigues , Thalita Maiara Patrício; Chaves , Camila Teixeira de Oliveira Penna; Oliveira, Marília Reis dos Santos de (Seven Editora, 2023)
Duchenne muscular dystrophy (DMD) is a neuromuscular pathology, being the most serious, rare and hereditary. Patients present muscoskeletal, respiratory, cardiac and orthopedic complications. Due to these muscular changes, these patients may develop urinary incontinence, which is loss of bladder control and any involuntary loss of urine. The objective of this study was to understand how urinary incontinence can affect the lives of sufferers. In the search for answers, we used a bibliographic review, where the data was found in a qualitative way, through scientific articles between the years 2003 and 2022, based on GOOGLE ACADÊMICO, PUD MED, SCIELO AND BOOKS. Studies and bibliographical analyzes were carried out where it was possible to state the proportion of interruptions in people who present the disease, such as disabling the achievement of goals of physiological functioning where a greater concentration is involved in the segment of urinary incontinence, in this way associated questions were practiced whether the The lives of individuals with this pathology and its changes can cause harm that can lead to psychological damage and integration. I believe that in the future it will be possible to achieve guidance and contributions that benefit people with the pathology. DOI:https://doi.org/10.56238/sevened2023.006-005